Urgensi Pembaruan Hukum Pidana terhadap Tindak Pidana Siber Berbasis Kecerdasan Buatan (Artificial Intelligence) di Indonesia - Fajar Hadi; Moh. Lubsi Tuqo Romadhan (AHKAM, 2026)
Although corporate liability has received attention in various studies, research specifically deconstructing the theory of fault arising from the autonomization of artificial intelligence (Artificial Intelligence/AI) through an Islamic legal theology approach remains limited. This study aims to analyze the weaknesses of Indonesian criminal law in responding to AI-based cybercrime and to formulate directions for its reform. This study employed a qualitative approach with a normative juridical design that examined selected legal and policy documents through purposive literature searching. Data were collected through the documentation of legal materials and analyzed using content analysis and teleological interpretation. The findings showed that the doctrine of derived intent under Article 49 of the Criminal Code (KUHP) has reached an impasse because it is unable to encompass autonomous machine actions (emergent behavior) and has the potential to generate automation bias and problems related to algorithmic opacity (black box). These findings strengthen the development of corporate liability theory and broaden the understanding of AI governance in criminal law. This study concludes that the doctrine of fault needs to be reconstructed into structural fault based on corporate culture (corporate culture liability) and grounded in Qur’anic ethics. Theoretically, this study contributes to the development of the literature on cyber law and corporate liability, while practically, its findings can serve as a foundation for the Government, DPR, Polri, and Komdigi in formulating regulations concerning AI due diligence obligations and algorithmic audits. Future research should develop empirical sociolegal studies on the technological competence of law enforcement officers in handling AI-based cybercrime.